Cultural Values and Their Role in Shaping the Adaptation of Realistic Mathematics Education (RME) in Indonesia: A Mixed-Methods Approach - Abbas, Sagir Adamu; Quiño, Annabelle M.; Abraham, Nayantara (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The main objective of the study is to analyze how cultural factors influence the implementation of RME in the context of mathematics education in Indonesia. Methodology: The method used is a qualitative study employing content/document analysis of curriculum guidelines and instructional materials. Additionally, semi-structured interviews were conducted with six educators, and non-participant observations were carried out in three schools to examine the implementation of Realistic Mathematics Education (RME). Main Findings: The results of the study showed that the success of RME adaptation was influenced by local cultural values, such as community-based approaches and the context of students' daily lives. Novelty/Originality of this study: The novelty of this research lies in the in-depth analysis of the interaction between RME principles and Indonesian cultural characteristics, providing new insights into the development of more contextual and effective mathematics learning strategies.